Just after midnight : a novel - Hyde, Catherine Ryan (Lake Union Publishing, 2018)
A woman navigating a difficult separation accompanies a traumatized teen along the horse-show circuit to help the latter reconnect with a beloved mare and come to terms with violent memories.